La familia y su incidencia en el rendimiento escolar en los alumnos del séptimo año de educación básica de la Escuela Fiscal Mixta Dr. Leopoldo Muñoz Rodríguez de la ciudad de Machala durante el periodo lectivo 2012-2013. - Rambay León, Iván Felipe (2013)
UN has conducted quantitative and qualitative analysis of the results obtained by the methods and techniques of scientific research, a survey was applied to Students and Parents, As Fieldwork in the institution.